A ternary heterogeneous structure photocatalyst and preparation method thereof

By growing ultra -thin NIOX nanoscopic tablets on ZNO/MOOX nano sticks, the three -way heresy structure photocatalyst Zno/MOOX@niox is formed to solve the lack of existing semiconductor photocatalysts in the separation of photogenic charge and spectral range, and achieve efficient efficiency The optical catalytic performance and stability.

CN115845864BActive Publication Date: 2025-01-28CHENGDU YALIAN TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211461903.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-22
Publication Date
2025-01-28
Estimated Expiration
2042-11-22

AI Technical Summary

Technical Problem

Existing semiconductor photocatalysts have shortcomings in photogenerated charge separation and spectral range, resulting in limited application areas.

Method used

By growing ultra -thin NIOX nanoscope on ZNO/MOOX nano sticks, a ternary heresy structural optical catalyst Zno/MOOX@Niox is formed to improve its light absorption and anti -light corrosion performance.

Benefits of technology

It significantly improves the optical catalytic performance, especially the output of O2 under the visible optical light reached 3770 molh-1G, and the material shows high stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115845864B_ABST
    Figure CN115845864B_ABST
Patent Text Reader

Abstract

The present invention provides a ternary heterogeneous structure photocatalyst, which forms a heterogeneous structure nanocomposite material ZnO / MoOx@NiOx by coupling two-dimensional NiOx nanosheets (NSs) with MoOx@ZnO, and the nanocomposite material ZnO / MoOx@NiOx contains epitaxial nanosheets. The present invention also provides a method for preparing a ternary heterogeneous structure photocatalyst, comprising the following steps: step 1, synthesizing zinc oxide nanorods; step 2, preparing ZnO / MoOx hybrid nanorods; step 3, functionalizing ZnO / MoOx hybrid nanorods; step 4, preparing heterogeneous structure ZnO / MoOx@NiOx core-shell nanorods.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new energy catalysts, and in particular to a ternary heterogeneous structure photocatalyst and a preparation method thereof. Background Art

[0002] Over the past few decades, semiconductor photocatalysis has received extensive attention as one of the most promising pathways for alternative fuel production in future green energy production devices. One of the key reasons that hinder the interplay of semiconductor photocatalysis in the field of practical application is their poor ability to separate photogenerated charges. Another major issue is the small spectral range in which semiconductors accept light harvesting. From this perspective, focusing on various semiconductor properties, zinc oxide is a widely characterized material with well-known favorable properties such as high electron mobility and non-toxicity, high excitation energy, wide band gap (by virtue of its piezoelectric properties), and n-type semiconductor capability. So far, many nanostructures of zinc oxide have been synthesized, including nanorods, nanoparticles, nanoplates, nanowires, and urchin-like structures. However, due to the inability to separate photogenerated charges, light can only be harvested in the ultraviolet spectral region, which hinders the extension of the scale of its application field, so the synthesis of high-performance zinc-based semiconductor photocatalysts remains a challenging task. Summary of the invention

[0003] In view of the deficiencies in the prior art, the present invention provides a ternary heterostructure photocatalyst and a preparation method thereof, designs a metal oxide semiconductor with good light absorption and light corrosion resistance, and can effectively improve the photocatalytic performance.

[0004] The above technical objectives of the present invention are achieved through the following technical solutions:

[0005] A ternary heterostructure photocatalyst: A heterostructure nanocomposite material ZnO / MoOx@NiOx is formed by coupling two-dimensional NiOx nanosheets (NSs) with MoOx@ZnO, and the nanocomposite material ZnO / MoOx@NiOx includes epitaxial nanosheets.

[0006] The present invention also provides a method for preparing a ternary heterogeneous structure photocatalyst, comprising the following steps:

[0007] Step 1, synthesizing zinc oxide nanorods;

[0008] Step 2: Preparation of ZnO / MoOx hybrid nanorods

[0009] Step 3, functionalization of ZnO / MoOx hybrid nanorods;

[0010] Step 4, preparation of heterostructured ZnO / MoOx@NiOx core-shell nanorods.

[0011] The present invention is further configured as follows: zinc acetate (Zn(Ac)2.2H2O) and sodium hydroxide (NaOH) are prepared in ethanol of different concentrations, 10 mL of a zinc acetate solution having a concentration of 0.1 M is combined with 20 mL of sodium hydroxide having a concentration of 0.5 M to prepare a transparent solution, the transparent solution is transferred to a stainless steel autoclave, and hydrothermally treated at 100-150° C. for 24 hours, and finally the prepared white product is collected by centrifugation, washed with distilled water and anhydrous ethanol, and dried in a vacuum oven.

[0012] The present invention is further configured as follows: 200 mg of zinc oxide nanorods are added to 30 mL of water, and (NH4)6Mo7O2 is added, the suspension is vigorously stirred at 60-70°C for 1-2 hours, and then washed with dilute ethanol and distilled water for multiple times, the purified sample is dried in a vacuum oven at 50-60°C, and calcined at 180-200°C for 0.5-1 hour under a N2 atmosphere.

[0013] The present invention is further configured as follows: ZnO / MoOx hybrid nanorods (100 mg) are dispersed in 40 ml of ethanol containing 300 mg of polyvinyl pyrrolidone (PVP, Mw=40000), and stirred and dispersed uniformly for 12 hours, and then the PVP-functionalized zinc oxide nanorods are washed with ethanol for multiple times, and zinc oxide nanorods without PVP are collected. Finally, the obtained ZnO / MoOx nanorods are heated at 80-100° C. for 1-3 hours.

[0014] The present invention is further configured as follows: 20 mg of functionalized ZnO / MoOx hybrid nanorods are dispersed in a mixture of 20 mL of ethanol and 60 mL of deionized water for half an hour, and then 0.4 mmol of Ni(NO)3·6H2O2 is added as a Ni precursor, and after 0.7 mmol of hexamethyltetramine and 0.1 mmol of trisodium citrate are added, the mixture is continuously stirred for 0.5-1 hour, and then the mixture is refluxed in an oil bath at 80-100° C. for 3-7 hours and vigorously stirred; the product is collected by centrifugation, washed with dilute ethanol for multiple times, and then dried in a vacuum oven at 60-70° C. for 10 hours, and the final product is calcined again at 250-300° C. at a heating rate of 5C / min for 2 hours to synthesize heterostructured ZnO / MoOx@NiOx core-shell nanorods.

[0015] The present invention is further configured as follows: zinc acetate (Zn(Ac)2.2H2O) and sodium hydroxide (NaOH) are prepared in ethanol of different concentrations, 10 mL of a 0.1 M zinc acetate solution is combined with 20 mL of a 0.5 M sodium hydroxide solution to prepare a transparent solution, the transparent solution is transferred to a stainless steel autoclave, and hydrothermally treated at 150° C. for 24 hours, and finally the prepared white product is collected by centrifugation, washed with distilled water and anhydrous ethanol, and dried in a vacuum oven.

[0016] The present invention is further configured as follows: 200 mg of zinc oxide nanorods are added to 30 mL of water, and (NH4)6Mo7O2 is added, the suspension is vigorously stirred at 70°C for 2 hours, and then washed with dilute ethanol and distilled water for multiple times, the purified sample is dried at 60°C in a vacuum oven, and calcined at 200°C for 1 hour under a N2 atmosphere.

[0017] The present invention is further configured as follows: ZnO / MoOx hybrid nanorods (100 mg) are dispersed in 40 ml of ethanol containing 300 mg of polyvinyl pyrrolidone (PVP, Mw=40000), and stirred and dispersed uniformly for 12 hours, and then the PVP-functionalized zinc oxide nanorods are washed with ethanol for multiple times, and zinc oxide nanorods without PVP are collected. Finally, the obtained ZnO / MoOx nanorods are heated at 100° C. for 3 hours.

[0018] The present invention is further configured as follows: 20 mg of functionalized ZnO / MoOx hybrid nanorods are dispersed in a mixture of 20 mL of ethanol and 60 mL of deionized water for half an hour, and then 0.4 mmol of Ni(NO)3·6H2O2 is added as a Ni precursor, and after 0.7 mmol of hexamethyltetramine and 0.1 mmol of trisodium citrate are added, the mixture is continuously stirred for half an hour, and then the mixture is refluxed in an oil bath at 100° C. for 3-7 hours with vigorous stirring; the product is collected by centrifugation, washed with dilute ethanol for multiple times, and then dried in a vacuum oven at 70° C. for 10 hours, and the final product is calcined again at 300° C. at a heating rate of 5C / min for 2 hours to synthesize heterostructured ZnO / MoOx@NiOx core-shell nanorods.

[0019] The present invention has the following beneficial effects

[0020] By using ZnO / MoO x Ultrathin NiOx nanosheets grown on nanorods have been used to prepare an efficient ternary heterostructure visible light photocatalyst ZnO / MoOx@NiOx. The composition and structure of the heterojunction hybrid materials can be tuned by synthetic methods. These different structures have abundant reaction sites and extensive surface areas on closely prepared non-uniform coatings and ultrathin nanosheets to accelerate the separation and transport of photogenerated carriers. x As a bridge between ZnO and NiOx, it significantly improves the production of O2 and exhibits high stability. The main function of molybdenum oxide enables the built-in electric field at the interface to accelerate the charge transfer between zinc oxide and nickel oxide, which not only accelerates the interfacial charge separation, but also improves the catalytic reaction. Under visible light irradiation, O2 can reach an excellent 3770molh-1g. The improvement in the light efficiency of ZnO / MoOx@NiOx is due to the closeness of the interface contact. The efficient separation of carriers can be seen through transient optical flux spectroscopy, photoluminescence and electrochemical impedance spectroscopy. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 Schematic diagram summarizing the preparation of ZnO NR, ZnO / MoOx, and ZnO / MoOx@NiOx heterostructure photocatalysts;

[0022] Figure 2 FESEM images of pure ZnO nanorods (a), ZnO@MoOx (b), and ZnO / MoOx@NiOx (c, d), and FESEM images of XPS spectra of Mo3d (e) and Ni 2p in Zn / MoOx@NiOx (f);

[0023] Figure 3 TEM images (a, b), HRTEM images (c) and TEM images of ZnO / MoOx@NiOx nanorods (d), and elemental mapping results of Zn, NiMo and O2 (e);

[0024] Figure 4 Stepwise quenching efficiency of the three samples prepared for ZnO, ZnO / MoOx and ZnO / MoOx (c), band gap energy (b), IPCE spectra and steady-state PL spectra (e) and time-resolved PL decay graphs of ZnO, ZnO / MoOx and ZnO / ZnO / MoOx@NiOx samples (f);

[0025] Figure 5 Figure 3 Photocatalytic O2 evolution (a), comparison of the photocatalytic activities of the samples (b), photocurrent responses of ZnO and MoO@NiOx thin films (c), and electrochemical impedance spectroscopy of bare ZnO nanorods, ZnO, and ZnO / MoO@NiOx in the presence and absence of light (d). DETAILED DESCRIPTION

[0026] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and embodiments.

[0027] A method for preparing the ternary heterostructure photocatalyst as claimed in claim 1, comprising the following steps:

[0028] Step 1, synthesizing zinc oxide nanorods;

[0029] Step 2: Preparation of ZnO / MoOx hybrid nanorods

[0030] Step 3, functionalization of ZnO / MoOx hybrid nanorods;

[0031] Step 4, preparation of heterostructured ZnO / MoOx@NiOx core-shell nanorods.

[0032] In step 1, zinc acetate (Zn(Ac)2.2H2O) and sodium hydroxide (NaOH) are prepared in ethanol of different concentrations, 10 mL of 0.1 M zinc acetate solution is combined with 20 mL of 0.5 M sodium hydroxide to prepare a transparent solution, the transparent solution is transferred to a stainless steel autoclave, and hydrothermally treated at 100-150° C. for 24 h. Finally, the prepared white product is collected by centrifugation, washed with distilled water and anhydrous ethanol, and dried in a vacuum oven.

[0033] In step 2, 200 mg of zinc oxide nanorods were added to 30 mL of water, and (NH4)6Mo7O2 was added. The suspension was vigorously stirred at 60-70°C for 1-2 h, and then washed with dilute ethanol and distilled water several times. The purified sample was dried in a vacuum oven at 50-60°C and calcined at 180-200°C for 0.5-1 h under N2 atmosphere.

[0034] In step 3, ZnO / MoOx hybrid nanorods (100 mg) were dispersed in 40 ml of ethanol containing 300 mg of polyvinyl pyrrolidone (PVP, Mw = 40000), and stirred for uniform dispersion for 12 h, and then the PVP-functionalized zinc oxide nanorods were washed with ethanol several times, and the zinc oxide nanorods without PVP were collected. Finally, the obtained ZnO / MoOx nanorods were heated at 80-100°C for 1-3 h.

[0035] In step 4, 20 mg of functionalized ZnO / MoOx hybrid nanorods are dispersed in a mixture of 20 mL of ethanol and 60 mL of deionized water for half an hour, and then 0.4 mmol Ni(NO)3·6H2O2 is added as a Ni precursor, 0.7 mmol hexamethyltetramine and 0.1 mmol trisodium citrate are added, and the mixture is stirred for 0.5-1 hour, and then the mixture is refluxed in an oil bath at 80-100°C for 3h, 5h and 7h respectively, and stirred vigorously; the product is collected by centrifugation, washed with dilute ethanol several times, and then dried in a vacuum oven at 60-70°C for 10h, and the final product is calcined again at 250-300°C at a heating rate of 5C / min for 2h to synthesize heterostructured ZnO / MoOx@NiOx core-shell nanorods.

[0036] In summary, by x Ultrathin NiOx nanosheets grown on nanorods have been used to prepare an efficient ternary heterostructure photocatalyst ZnO / MoOx@NiOx for visible light-driven water splitting. The composition and structure of the heterojunction hybrid materials can be tuned by synthetic methods. These different structures have abundant reaction sites and extensive surface areas on closely prepared heterogeneous coatings and ultrathin nanosheets to accelerate the separation and transport of photogenerated carriers. xAs a bridge between ZnO and NiOx, it significantly improves the production of O2 and exhibits high stability. The main function of molybdenum oxide enables the built-in electric field at the interface to accelerate the charge transfer between zinc oxide and nickel oxide, which not only accelerates the interfacial charge separation, but also improves the catalytic reaction. Under visible light irradiation, O2 can reach an excellent 3770molh-1g. The improvement in the light efficiency of ZnO / MoOx@NiOx is due to the closeness of the interface contact. The efficient separation of carriers can be seen through transient optical flux spectroscopy, photoluminescence and electrochemical impedance spectroscopy.

[0037] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.

Claims

1. A ternary heterostructure photocatalyst, characterized in that: The heterostructured nanocomposite ZnO / MoOx@NiOx is formed by coupling two-dimensional NiOx nanosheets with MoOx@ZnO, and the nanocomposite ZnO / MoOx@NiOx includes epitaxial nanosheets; The preparation method of the ternary heterogeneous structure photocatalyst comprises the following steps: Step 1, synthesizing zinc oxide nanorods; Zinc acetate and sodium hydroxide were prepared in ethanol with different concentrations, the zinc acetate solution was combined with sodium hydroxide to prepare a transparent solution, the transparent solution was transferred to a stainless steel autoclave, and hydrothermally treated at 100-150° C. for 24 h, and finally the prepared white product was collected by centrifugation, washed with distilled water and anhydrous ethanol, and dried in a vacuum oven; Step 2, preparing ZnO / MoOx hybrid nanorods; The zinc oxide nanorods were added to water and (NH4)6Mo7O2 was added. The suspension was vigorously stirred at 60-70℃ for 1-2h, then washed with dilute ethanol and distilled water several times. The purified sample was dried in a vacuum oven at 50-60℃ and calcined at 180-200℃ for 0.5-1h under N2 atmosphere. Step 3, functionalization of ZnO / MoOx hybrid nanorods; The ZnO / MoOx hybrid nanorods were dispersed in ethanol containing polyvinyl pyrrolidone and stirred for 12 h, and then the PVP-functionalized zinc oxide nanorods were washed with ethanol several times, and the PVP-free zinc oxide nanorods were collected. Finally, the obtained ZnO / MoOx nanorods were heated at 80-100 °C for 1-3 h. Step 4, preparation of heterostructured ZnO / MoOx@NiOx core-shell nanorods; Functionalized ZnO / MoOx hybrid nanorods were dispersed in a mixture of ethanol and deionized water for half an hour, and then Ni(NO)3·6H2O2 was added as a Ni precursor. After adding hexamethyltetramine and trisodium citrate, the mixture was stirred for 0.5-1 hour, and then the mixture was refluxed in an oil bath at 80-100ºC for 3-7 hours with vigorous stirring; the product was collected by centrifugation and washed several times with dilute ethanol, and then dried in a vacuum oven at 60-70°C for 10 hours. The final product was calcined again at 250-300ºC at a heating rate of 5 C / min for 2 hours to synthesize heterostructured ZnO / MoOx@NiOx core-shell nanorods.

2. The ternary heterostructure photocatalyst according to claim 1, characterized in that: In step 1, zinc acetate and sodium hydroxide are prepared in ethanol of different concentrations, 10 mL of a 0.1 M zinc acetate solution is combined with 20 mL of a 0.5 M sodium hydroxide solution to prepare a transparent solution, the transparent solution is transferred to a stainless steel autoclave, and hydrothermally treated at 100-150° C. for 24 h, and finally the prepared white product is collected by centrifugation, washed with distilled water and anhydrous ethanol, and dried in a vacuum oven.

3. The ternary heterostructure photocatalyst according to claim 1, characterized in that: In step 2, 200 mg of zinc oxide nanorods were added to 30 mL of water, and (NH4)6Mo7O2 was added. The suspension was vigorously stirred at 60-70°C for 1-2 h, and then washed with dilute ethanol and distilled water several times. The purified sample was dried in a vacuum oven at 50-60°C and calcined at 180-200°C for 0.5-1 h under N2 atmosphere.

4. The ternary heterostructure photocatalyst according to claim 1, characterized in that: In step 3, 100 mg of ZnO / MoOx hybrid nanorods were dispersed in 40 ml of ethanol containing 300 mg of polyvinyl pyrrolidone and stirred for uniform dispersion for 12 h. The PVP-functionalized zinc oxide nanorods were then washed with ethanol several times, and the PVP-free zinc oxide nanorods were collected. Finally, the obtained ZnO / MoOx nanorods were heated at 80-100°C for 1-3 h.

5. The ternary heterostructure photocatalyst according to claim 1, characterized in that: In step 4, 20 mg of functionalized ZnO / MoOx hybrid nanorods were dispersed in a mixture of 20 mL of ethanol and 60 mL of deionized water for half an hour, and then 0.4 mmol Ni(NO)3·6H2O2 was added as a Ni precursor. After adding 0.7 mmol hexamethyltetramine and 0.1 mmol trisodium citrate, the mixture was stirred for 0.5-1 hour, and then the mixture was refluxed in an oil bath at 80-100ºC for 3-7 hours with vigorous stirring; the product was collected by centrifugation and washed several times with dilute ethanol, and then dried in a vacuum oven at 60-70°C for 10 hours. The final product was calcined again at 250-300ºC at a heating rate of 5 C / min for 2 hours to synthesize heterostructured ZnO / MoOx@NiOx core-shell nanorods.

6. The ternary heterostructure photocatalyst according to claim 2, characterized in that: Zinc acetate and sodium hydroxide were prepared in ethanol of different concentrations. 10 mL of 0.1 M zinc acetate solution was combined with 20 mL of 0.5 M sodium hydroxide to prepare a transparent solution. The transparent solution was transferred to a stainless steel autoclave and hydrothermally treated at 150 °C for 24 h. Finally, the prepared white product was collected by centrifugation, washed with distilled water and anhydrous ethanol, and dried in a vacuum oven.

7. The ternary heterostructure photocatalyst according to claim 3, characterized in that: 200 mg of zinc oxide nanorods were added to 30 mL of water, and (NH4)6Mo7O2 was added. The suspension was vigorously stirred at 70°C for 2 h and then washed several times with dilute ethanol and distilled water. The purified sample was dried in a vacuum oven at 60°C and calcined at 200°C for 1 h under N2 atmosphere.

8. The ternary heterostructure photocatalyst according to claim 4, characterized in that: 100 mg of ZnO / MoOx hybrid nanorods were dispersed in 40 ml of ethanol containing 300 mg of polyvinyl pyrrolidone and stirred for uniform dispersion for 12 h. Then, the PVP-functionalized zinc oxide nanorods were washed with ethanol several times, and the PVP-free zinc oxide nanorods were collected. Finally, the obtained ZnO / MoOx nanorods were heated at 100 °C for 3 h.

9. The ternary heterostructure photocatalyst according to claim 5, characterized in that: 20 mg of functionalized ZnO / MoOx hybrid nanorods were dispersed in a mixture of 20 mL of ethanol and 60 mL of deionized water for half an hour, and then 0.4 mmolNi(NO)3·6H2O2 was added as a Ni precursor. After adding 0.7 mmol hexamethyltetramine and 0.1 mmol trisodium citrate, the mixture was stirred for half an hour, and then the mixture was refluxed in an oil bath at 100ºC for 3-7 hours with vigorous stirring; the product was collected by centrifugation and washed several times with dilute ethanol, and then dried in a vacuum oven at 70°C for 10 h. The final product was calcined again at 300°C for 2 hours at a heating rate of 5C / min to synthesize heterostructured ZnO / MoOx@NiOx core-shell nanorods.

Citation Information

Patent Citations

  • Nickel oxide nanosheet and bismuth molybdate nanofiber heterojunction photocatalytic material as well as preparation method and application thereof

    CN112619659A